Emergence of Human Rotavirus Group A Genotype G9 Strains, Wuhan, China - Yang, Jihong (Centers for Disease Control and Prevention, 2007)
Of 322 stool specimens collected from children with diarrhea from October 2005 through September 2006 in Wuhan, China, group A rotavirus was identified in 101 (31.4%). The most prevalent group A rotavirus genotype was G3P[8] (62.6%), followed by G1P[8](17.6%), G1+G3P[8](8.8%), G3P[4](6.6%), G1P[4](2.2%), and G9P[8](2.2%). The G9 strains were first detected in Wuhan.